A socio-ecological appraisal of perceived risks associated with mangrove (Mānawa) management in Aotearoa New Zealand. Issue 3 (3rd July 2022) - Le Heron, Richard; Lundquist, Carolyn J.; Logie, June; Blackett, Paula; Heron, Erena Le; Awatere, Shaun; Hyslop, Jade
ABSTRACT: Why have mangroves and their ecosystems been so hotly contested over the last quarter century in Aotearoa New Zealand's northern waters? Central to 'mangrove mania' are multiple, competing and often antagonistic perceptions of the perceived risks posed by mangrove presence, their removal and efforts to restore them. Not surprisingly this has led to a chaotic mangrove knowledge space, with significant gaps in knowledge required to understand risks associated with mangrove management. In a socio-ecological investigation of risk questions relating to the mangrove debate, we reveal how localised contestations of mangroves have been 'arbitrated' – in different directions. This state of affairs has resulted from several critical threads: from many sources, pressures and intentions, but all involving the often ill-specified lens of public opinion, science practice, environmental management procedures, Māori knowledge, community views, land and inshore development, and consenting processes. We systematically examine the trajectory of these critical threads and their interactions, underlying the mangrove debate and the resulting variability in how risks are portrayed. Our evidence suggests that perceived risk of mangrove expansion, and of mangrove removal impacts, is contested and linked to different desired and imagined futures.